Vias de sinalização ativadas pela alamandina em cardiomiócitos - Itamar Couto Guedes de Jesus (2016)
The renin angiotensin system consists of a series of peptides, enzymes and receptors that are responsible for the control of renal and cardiovascular function. In recent years, this system has undergone a number of modifications with the discovery of new members. Alamandine is a heptapeptide recently characterized that can be formed from angiotensin A or angiotensin- (1-7), which presents various biological functions including in the heart. Although there is already a generated knowledge about functions of this new peptide, it is not known by which intracellular pathways these effects are developed. Therefore, in this research our goal was to investigate the intracellular signaling pathways triggered by alamandine in cardiomyocytes from healthy and hypertensive animal models. Additionally, we aimed to investigate whether alamandine is able to protect neonatal rat cardiomyocytes against angiotensin II hypertrophic effects. The results show that alamandine induces the production of nitric oxide (NO) in adult cardiomyocytes, and this effects occurs in parallel with increases in phosphorylation of LKB1 and AMPKα. This NO raise induced by alamandine was observed in cardiomyocytes from MAS knockout mice, and it was abolished in cardiomyocytes from MrgD knockout mice or in cells treated with D-PRO7. When AMPKα was inhibited, alamandine induced NO production in cardiomyocytes was abolished. In isolated cardiac myocytes from an animal model of hypertension, alamandine also activated LKB1/AMPKα. In neonatal cardiomyocytes, alamandine was able to exert an anti-hypertrophic effect in Ang II treated cells. The anti-hypertrophic effect of alamandine in cells treated with Ang II was blocked in the presence of MrgD receptor antagonist, or in the presence of nitric oxide synthase inhibitor. Moreover we found that AMPKα inhibitor, Compound C was also effective on blocking alamandine protective signaling against Ang II. Thus, these data infer that the alamandine exerts its effects in cardiac myocytes via MrgD/AMPKα/NO signaling pathway. Taken together, our data indicate an important role of alamandine, and highlights its therapeutic potential.